Influence of post-harvest application of Stenotrophomonas rhizophila on quality of mango cv. BARI Aam-3 (Bangladesh Journal of Agriculture, 2023)
The study was conducted at the Postharvest and Plant Biotechnology Laboratory, Department of Horticulture, Patuakhali Science and Technology University, Patuakhali, Bangladesh during the period from July to December 2018 to study the biocontrol performance of selected antagonistic bacteria Stenotrophomonas rhizophila strain PSTU-Hort-14 on BARI Aam-3. All the treatments were arranged in a completely randomized design (CRD) with five replications and repeated twice. The bacterial strain PSTU-Hort-14 was found highly compatible with 20% lemongrass extract and 2% sodium bicarbonate (SBC) or mixture of both which reduced 96.5% of the disease over control in naturally infected fruits at the end of 14 days of storage at 12±1ºC and 90±5% RH. The combined treatments of Stenotrophomonas rhizophila-lemongrass extract-SBC showed reduced weight loss by more than 25% compared to the control at 12±1ºC and 90±5% RH. The shelf life was thus extended by 15 days compared to control at 12±1ºC and 90±5% RH. Finally, it was clear that the strain Stenotrophomonas rhizophila strain PSTU-Hort-14 was effective when incorporated with 2% SBC and 20% lemongrass extract to control C. gloeosporioides as well as improve the postharvest quality of BARI Aam-3 during cold storage.Bangladesh J. Agri. 2023, 48(2): 13-29